Prognostic value of coupling interval, prematurity index and heart rate variability in Boxer dogs - Carvalho, Elizabeth Regina [UNESP]; Zacché, Evandro [UNESP]; Fenerich, Michelli [UNESP]; Camacho, Aparecido Antônio [UNESP]; Sousa, Marlos G. (FapUNIFESP (SciELO), 2019)
Boxer dogs with arrhythmogenic right ventricular cardiomyopathy (ARVC) can experience sudden cardiac death regardless of presence/absence of clinical signs. The aims of this retrospective study were two-fold: 1) to investigate the coupling interval (CI) and prematurity index (PI) of ventricular arrhythmias (VA), and the heart rate variability (HRV) in Boxers, and 2) to evaluate their impact on overall survival time. The first 24-hour Holter 36 client-owned Boxer dogs meeting inclusion/exclusion criteria were evaluated for the number, morphology, site of origin, complexity, CI and PI, of ventricular premature complexes (VPCs), and time domain HRV. The effect on survival was assessed, considering the presence/absence of ventricular tachycardia (VT), and syncope. All-cause mortality was considered as the end-point, with median survival times being obtained by Kaplan-Meier analyses and compared by log-rank test. Polymorphic VPCs were more common in symptomatic dogs than asymptomatic. VPCs in dogs with VT were less premature, due to the influence of heart rate on PI despite comparable CI. The PI and mean heart rate (HRme) were significantly different between VT and non-VT dogs but did not discriminate adequately between groups as standalone tests. Median survival time was shorter in Boxer dogs with VT (463 vs 1645 days, HR: 4.31, P=0.03). The HRV parameters, SDNN and SDANN, were both associated with prognosis. The CI and PI were not demonstrated to be prognostic surrogates in Boxer dogs with VA. HRme≥112bpm is 100% sensitive but only 46% specific for detecting VT in Boxers on the 24-hour Holter. Presence of VT, SDNN≤245ms, or SDANN≤134ms at the time of the first 24-hour Holter was associated with a shorter survival.
Keywords: Arrhythmias; Boxer dogs; Coupling interval; Dogs; Heart rate; Prematurity index; Prognostic; Sudden death; Sympathetic nervous system